MODEL PEMBELAJARAN ARGUMENT DRIVEN INQUIRY (ADI) BERBANTUAN WORDWALL TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Eka Yuniar, Nuril; Rachmadtullah, Reza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is based on the low critical thinking ability of elementary school students, which is characterized by the lack of activity and courage of students in expressing their opinions during the learning process. This research aims to analyze the application and influence of the Argument Driven Inquiry (ADI) learning model with the help of Wordwall media on the critical thinking ability of grade V elementary school students. The ADI model was chosen because it provides space for students to analyze evidence and build arguments systematically. The research method used is quantitative with a quasi-experimental design of posttest-only control group design. The research subject consists of 40 students in class V of SDN Dukuh Menanggal 1 Surabaya. The data collection technique is carried out through observation and test, which is then analyzed using t-test (independent sample t-test) through the SPSS application version 21. The results of the data analysis show a significance value (2-tailed) of 0.000. Because p-value < 0.05, then ho is rejected and ha is accepted. The results prove that there is a significant influence from the implementation of the Wordwall-assisted Argument Driven Inquiry (ADI) learning model on the critical thinking skills of elementary school students. Wordwall media is effective in supporting the inquiry stage and increasing student interactive involvement in learning.